Respuesta :
Answer:
Therefore values of a and b are
[tex]a=3\ and\ b = 2[/tex]
Step-by-step explanation:
Rewrite [tex]x^{2}-6x+7=0[/tex] in the form
[tex](x-a)^{2}=b[/tex]
where a and b are integers,
To Find:
a = ?
b = ?
Solution:
[tex]x^{2}-6x+7=0[/tex] ..............Given
Which can be written as
[tex]x^{2}-6x=-7[/tex]
[tex](\frac{1}{2} coefficient\ of\ x)^{2}=(\frac{1}{2}\times -6)^{2}=9[/tex]
Adding half coefficient of X square on both the side we get
[tex]x^{2}-6x+9=-7+9=2[/tex] ...................( 1 )
By identity we have (A - B)² =A² - 2AB + B²
Therefore,
[tex]x^{2}-6x+9=x^{2}-2\times 3\times x+3^{2}=(x-3)^{2}[/tex]
Substituting in equation 1 we get
[tex](x-3)^{2}=2[/tex]
Which is in the form of
[tex](x-a)^{2}=b[/tex]
On comparing we get
a = 3 and b = 2
Therefore values of a and b are
[tex]a=3\ and\ b = 2[/tex]